A study on the influence of scanning strategies on the levelness of the melt track in selective laser melting process of stainless steel powder - Le, Kim Quy (2020)
By using a numerical model for a selective laser melting process, this study investigates the melt pool behaviours and the resulting defects due to different scanning strategies. Two common scanning patterns were tested: sequential and boustrophedon. The study found that sequential scanning strategy leads to a non-flat printed surface, while the boustrophedon strategy produces a flat printed surface. At the beginning of the track, the molten material is pulled from the hot laser spot to the cold tail by the Marangoni force leading to an increase in the melt pool height of the sequential and alternated strategies. On the other hand, due to the deep keyhole and the high cooling rate when the laser is switched off, a recess is formed at the end of the tracks. Similar phenomena can be observed in the boustrophedon scanning strategy at the start and ending of the track.